Compatibility and competitiveness of a laboratory strain of Anastrepha fraterculus (Diptera: Tephritidae) after irradiation treatment - Allinghi, A. (2007)
We evaluated under semi-natural field cage conditions sexual compatibility and competitiveness of a laboratory strain (LAB) compared to a wild population (TUC) of Anastrepha fraterculus (Wiedemann). The LAB strain is produced under semi-mass rearing conditions at the Estación Experimental Agroindustrial Obispo Colombres facility (Tucumán, Argentina). Wild flies were obtained at Horco Molle (Tucumán, Argentina) from infested guava fruits. LAB pupae were irradiated (60Co) 48 h before adult emergence. The tested doses were 0 (control), 40, 70, and 100 Gy. Twenty-five males and 25 females each of TUC and LAB were released into cages and mating pairs collected. Only 1 irradiation dose was considered at a time. Females were separated and allowed to lay eggs into artificial fruits to estimate induced sterility from the corresponding hatching rate. Copulation start time did not differ significantly between strains nor among irradiation treatments. Copulation duration showed highly significant differences among irradiation doses, but no differences between strains. The index of sexual isolation (ISI) and the relative sterility index (RSI) indices indicated that LAB and TUC are fully compatible, males from TUC and LAB did not differ in mating competitiveness, and irradiation within the range tested did not affect these indices. Non-irradiated LAB females exhibited higher mating propensity than TUC ones. However, a significant reduction in the female relative performance index (FRPI) index was observed with increasing irradiation dose. The analysis of induced sterility indicated that treatment with 40 Gy reduces male fertility from about 80% to 0.75%, and higher doses produce total sterility. In females, the 40 Gy dose reduces fertility to about 2% and higher doses prevent egg laying.